Traffic speed and occupancy occurrence on the urban expressway between southbound and northbound / Nur Nabihah Abdul Rahman ... [et al.] - Abdul Rahman, Nur Nabihah; Md Diah, Jezan; Adnan, Muhammad Akram; Syed Abbas, Syed Khairi; Rosli, Adi Yazid (2024)
Economic growth in developed nations often leads to a surge in transportation needs, particularly in large cities. This can manifest as increased accident rates, environmental degradation, social strain, and most notably, traffic congestion. Addressing these challenges requires a multifaceted approach, balancing social, environmental, and economic considerations while prioritising public safety and health. The study contributes to the search for solutions by investigating traffic flow patterns on urban expressways. The research compares southbound and northbound lane speeds, analysing the relationship between speed and vehicle occupancy in both directions. By leveraging secondary quantitative data collected over seven consecutive days with Speedlane ProTM Counter Classifier radar technology, the study aims to identify potential causes of congestion. It is expected that the northbound lanes may experience higher traffic volume and greater variability compared to the southbound lanes. This research can inform traffic management strategies and contribute to reduced congestion in urban areas.